2005
DOI: 10.1016/j.immuni.2005.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of γδTCR Signaling Efficiently Diverts Thymocytes to the αβ Lineage

Abstract: The role of the T cell antigen receptor complex (TCR) in alphabeta/gammadelta lineage commitment remains controversial, in particular whether different TCR isoforms intrinsically favor adoption of a certain lineage. Here, we demonstrate that impairing the signaling capacity of a gammadeltaTCR complex enables it to efficiently direct thymocytes to the alphabeta lineage. In the presence of a ligand, a transgenic gammadeltaTCR mediates almost exclusive adoption of the gammadelta lineage, while in the absence of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
339
4
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(375 citation statements)
references
References 61 publications
21
339
4
1
Order By: Relevance
“…Thus, signal strength does not only determine the outcome of positive and negative selection of DP cells; it appears also to be an important feature of b-selection. It has been suggested that strong and weak signals at the b-selection checkpoint favor development towards the cd and ab T cell lineages, respectively [25,26]. Our data is in agreement with this conclusion in that a certain minimal signal strength is required for facilitating b-selection through the ab (HY-) TCR.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, signal strength does not only determine the outcome of positive and negative selection of DP cells; it appears also to be an important feature of b-selection. It has been suggested that strong and weak signals at the b-selection checkpoint favor development towards the cd and ab T cell lineages, respectively [25,26]. Our data is in agreement with this conclusion in that a certain minimal signal strength is required for facilitating b-selection through the ab (HY-) TCR.…”
Section: Discussionsupporting
confidence: 91%
“…It was also observed that IL-17-producing ␥/␦ T cells are hardly induced in immunized joints, their DLNs, non-DLNs, and spleens of SKG mice (data not shown) 10 days after immunization with CFA plus type II collagen. Given that TCR signals in SKG mice are attenuated because of a point mutation in ZAP-70 (21), and differentiation of ␥/␦ T cells needs a strong signal via the TCR (48,49), there may be some defects in ␥/␦ T cell differentiation in SKG mice. This speculation was supported by data showing impaired development of specific subsets of ␥/␦ T cells in ZAP-70-knockout mice (50).…”
Section: Discussionmentioning
confidence: 99%
“…The thymus produces functional ab nTreg and gd T cells from common early precursors that follow distinct developmental pathways [7,26] but that end up sharing the unconventional property of being positively selected on high avidity signals [35][36][37][38], which presumably reflects their self-reactivity [21,39,40]. While the different homing properties of the two T-cell subsets may prevent their interaction in various tissues, gd cells may often come into contact with Treg in peripheral lymphoid organs, namely the spleen and lymph nodes (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%